Nanoparticles in allergen immunotherapy. Issue 6 (December 2021) - Longo, Alessandra; Longo, Valeria; Colombo, Paolo
Abstract : Purpose of review: Allergen immunotherapy is the only recognized causal treatment for allergic disease that modulates the immune system toward a tolerogenic or desensitized state. Allergens or their derivative preparations are formulated with adjuvants of different origin and having diverse immunological functions, such as prolonged tissue release and specific immunomodulatory properties. In the last 2 decades, thanks to developments in the field of nanotechnology, more biosafe nanoscale materials have become available for use as pharmaceutical adjuvants in medical research. Recent findings: Nanomaterials possess unique and versatile properties which can be employed to develop drug carriers with safer profiles, better stability in physiological conditions and immunomodulatory properties. Nanoparticles can have an adjuvant effect per se or also when they are packed in structures whose physical–chemical properties can be handled in a way that also influences its release dynamics. In particular, it has been suggested that nanoparticle preparations can be put in complexes or loaded with allergens or allergenic extracts, opening the way to innovative paradigms. Summary: In this review, we analyze allergen/nanoparticle properties in terms of cytotoxicity, stability and immunogenic reaction in in-vitro and animal systems.